THE IMPACT AND EFFORTS TO COMBAT CORRUPTION ON INDONESIA'S ECONOMIC DEVELOPMENT - Vania Atika Putri Srg; Najwa Raisha Hrp; Puteri Humaira; M. Chazriel (CV. Radja Publika, 2025)
Corruption is a social problem that significantly impacts development and the economy in Indonesia. This practice arises from weak morals, weak oversight, a lack of transparency, and a culture of graft and nepotism within the government. This study uses a descriptive qualitative method with a literature review approach to analyze the causes, impacts, and efforts to eradicate corruption. The results show that corruption has a significant impact on decreasing public trust in the government, hampering development, and weakening national economic growth. Furthermore, corruption also causes social inequality and a decline in the quality of public services. Efforts to eradicate corruption can be carried out through improvements to the governance system, increased transparency, early anti-corruption education, and firm and consistent law enforcement. With comprehensive measures involving all levels of society, it is hoped that corruption in Indonesia can be reduced, thus enabling development to proceed more effectively and fairly.